1983
DOI: 10.1002/ajpa.1330620302
|View full text |Cite
|
Sign up to set email alerts
|

A study of the polymorphism and ethnic distribution differences of human serum paraoxonase

Abstract: The enzyme serum paraoxonase shows a polymorphism in Europeans which is governed by two alleles. The first allele has a gene frequency plow of 0.716-0.777, and is manifested as a low activity group in homozygotes. More than 50% of all European test subjects can be included in this group. A second allele with a gene frequency qhigh of 0.223-0.284 was found in typical European distributions and is manifested in both the form of a second heterozygotic and a third homozygotic group with high activities. The Hardy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[9] Variations in the distribution profile of these phenotypes among different ethnic groups have been observed. It has been shown to have unimodal distribution in Negroid and Mongoloids, bi-modal in European population[10] while West Germans and White Americans showed tri-modal distribution. [1112] Tri-modal distribution of total PON1 activity is also observed in the Indian population from Bombay and the surrounding area and among North-West Indian Punjabis.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Variations in the distribution profile of these phenotypes among different ethnic groups have been observed. It has been shown to have unimodal distribution in Negroid and Mongoloids, bi-modal in European population[10] while West Germans and White Americans showed tri-modal distribution. [1112] Tri-modal distribution of total PON1 activity is also observed in the Indian population from Bombay and the surrounding area and among North-West Indian Punjabis.…”
Section: Introductionmentioning
confidence: 99%
“…Marbling score was shown to be significantly higher in female and castrated male than in male, regardless of bovine species, indicating possible roles of sex hormones in the regulation of fat deposition [24,25]. The gender-dependent difference in serum PON1 levels of Hanwoo indicated a close relation with sex hormones, which was not observed in humans [26]. The positive association of serum PON1 levels with meat quality could be due to more males in the grade 3 than the other meat grade groups.…”
Section: Resultsmentioning
confidence: 99%
“…HDL-associated PON1 and ARE are the enzymes involved in such systems. These enzymes contribute to the detoxification of organophosphorus compounds and carcinogenic lipid-soluble radicals from lipid peroxidation [ 3 , 4 , 5 ]. Studies have revealed that PON1 expression is alleviated in human lung cancer [ 18 ] and pancreatic [ 19 ] and gastric cancers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum PON1 and ARE have been shown to function as a single enzyme [ 4 ]. Human serum PON1 indicates neither age-related changes in activity nor gender differences [ 5 ]. Reduced PON1 enzyme activities have been shown in several groups of patients with hypercholesterolaemia, diabetes mellitus, and cardiovascular disease, in which the patients are under increased oxidative stress [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%